Legal and Ethical Dimensions of Pension Fund Management: The Role of DSN-MUI Fatwas in Sharia and Conventional Systems - Rafif Hawari; Akbar Muhamad Ashoni (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2025)
Indonesia’s pension fund system operates within a dual financial framework consisting of conventional and Sharia-based schemes. While conventional pension funds prioritize investment flexibility and return maximization, Sharia pension funds emphasize compliance with Islamic legal and ethical principles. This duality raises important legal and ethical questions, particularly regarding the role of DSN-MUI fatwas as normative instruments within Indonesia’s positive legal system. This study employs a qualitative descriptive approach based on literature review, regulatory analysis, and examination of relevant fatwas and statutory regulations. Primary and secondary data were analyzed to compare the legal foundations, governance structures, investment mechanisms, and ethical dimensions of conventional and Sharia pension fund management in Indonesia. The findings reveal that conventional pension funds are primarily regulated by Law No. 11 of 1992 and OJK regulations, focusing on financial efficiency and market-based returns. In contrast, Sharia pension funds are governed by an additional normative framework derived from DSN-MUI fatwas, particularly Fatwa No. 88/DSN-MUI/XI/2013, which mandates the avoidance of riba, gharar, and maysir. Although DSN-MUI fatwas are not legally binding in a formal sense, their integration into regulatory policies and operational requirements—such as the establishment of Sharia Supervisory Boards—significantly influences governance practices, transparency, and participant protection. The study highlights that the incorporation of Sharia ethical principles through DSN-MUI fatwas enhances accountability, trust, and long-term sustainability in pension fund management. While conventional pension funds benefit from broader investment diversification, Sharia pension funds offer stronger ethical safeguards and lower risk exposure. The findings suggest that a synergistic legal framework integrating state regulation and Sharia ethics can strengthen Indonesia’s pension fund system by balancing financial performance with moral responsibility.